IMPROVING INDIVIDUAL TAXPAYER COMPLIANCE IN KUPANG CITY: A SYNERGY OF TAXPAYERS, ORGANIZATIONS, AND TAX TECHNOLOGY - Oktariyana, Made Denny; Junias, Donny Teguh Santoso (Jurnal Aplikasi Akuntansi, 2026)
This study analyzes the declining compliance level of individual taxpayers in reporting Annual Tax Returns at the Kupang Primary Tax Office (2020–2024). Despite a sharp increase in active taxpayers, the compliance rate fell drastically from 92.9% (2020) to 54.5% (2024). The research examines this decline by considering three factors: low tax comprehension, new Average Effective Rate (TER) regulations (PP No. 58/2023), and administrative constraints from the system transition to Coretax (PMK No. 81/2024). This research employs an analytical framework that synergizes Taxpayer, Organization, and Technology variables, using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The research results show key findings across these factors. The Organization Factor shows that Understanding of Tax Regulations and tax sanctions has a positive and significant influence on Individual Taxpayer Awareness; however, Tax Socialization has no significant impact. Furthermore, the Technology Factor emerged as a strong driver, with the Tax Administration System, Information System Quality, and Service Quality all having a positive and significant influence on Individual Taxpayer Awareness, affirming the crucial role of modern systems. Finally, the Human Factor plays a central role. Individual Taxpayer Awareness is proven to have a positive and significant influence on Individual Taxpayer Compliance with the highest path coefficient (0.603), making it the most dominant predictor in achieving compliance.